An IoT Based Novel Hybrid-Gamified Educational Approach to Enhance Student’s Learning Ability - Mahapatra, Sushil Kumar; Pattanayak, Binod Kumar; Pati, Bibudhendu; Laha, Suprava Ranjan; Pattnaik, Saumendra; Mohanty, Bibhuprasad (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Student’s have different level of learning ability due to social and economic aspect they came through their life. Thus it is very necessary to reveal the criteria based on which their learning ability can be improved. This paper investigates these criteria and tries to improve the learning ability of students using a novel gamified educational method. The Internet of Things (IoT) also utilized to collect information to establish a communication network and educational network in this novel gamified educational method. The suggested Educational approach made use of field methods and gamification of course module in an IoT setting for improving learning stages. The presented educational model is tested on engineering students for two course module. The result shows that the rate improvement in learning has almost doubled by utilizing this proposed educational model i.e. from 0.66 to 1.33.